Who benefits from fleet electrification? quantifying the costs and benefits of transportation electrification strategies from different perspectives - J.Andrew Kelly; Yulu Guo; J.Peter Clinch (Transportation Research Interdisciplinary Perspectives, 2025)
Many countries have ambitious fleet electrification targets as part of their decarbonisation strategies. The transition will involve government supports, upfront costs to the consumers, and substantial impacts on the existing transportation tax base. This paper analyses the costs and benefits of defined pathways toward the national passenger electric vehicle (EV) target in Ireland from the perspective of the consumer, the exchequer, and society as a whole. This shift from a single-focus cost-benefit analysis enables consideration of differing priorities and issues for each group and offers quantified analysis to support the design and evaluation of policy in terms of rates of fleet change, consumer incentives and grant schemes, rebalancing of exchequer revenue, and the dynamic refinement of EV policy. Results demonstrate that EVs can deliver substantial benefits for car purchasers and costs for the exchequer. A negative net social benefit (NSB) is estimated to 2030, however, this ignores the requirement to meet legally-binding climate and air abatement commitments that would arguably justify the omission of the cost of public funds thereby turning the NSB positive. Notably, the earlier delivery of the fleet electrification strategy assessed delivers three times the consumer benefits of the later EV adoption rate scenario. The analysis also highlights specific adjustments that could be adopted to improve the performance of the overall policy package, including insights for refining the electrification pathway strategy, further evidence for raising public awareness of EV benefits and costs, and recommended reforms for the tax system and EV grant scheme to achieve better revenue balance into the future.